„Miasto nigdy się nie kończy…”. Mroczne oblicze miasta w prozie Herty Müller - Głuszko-Boczoń, Estera (Studia Rossica Posnaniensia, 2024)
One of the recurring motifs in Herta Müllerʼs work is the experience of the city, which often becomes a space of threat, violence, uncertainty, and finally repression and death. The German Nobel Prize laureate describes urban spaces, where the fate of the city is intertwined with the fate of the protagonists, depicting a world of people who are downtrodden, lost, defeated, and yet not without hope. This article discusses selected works by Herta Müller, in which the multidimensional image of the city opens up new fields for reflection and allows us to gain insight into how a totalitarian state functions. The cities the author describes are reflective of all Romanian cities under the dictatorship of Nicolae Ceaușescu; they are places of depravity and terror. This article also explores the aesthetics of ugliness which affects the understanding of the role of cities in Herta Müllerʼs prose, and analyzes important urban symbols such as asphalt, apartment blocks, parks and the flora and fauna characteristic of communist cities. In many of Müllerʼs texts, cities form a dramatic backdrop for acts of violence and repression against ‘the Stranger’ – for instance, the German minority, the Roma community, and women. Thus, the experience of an individual becomes the experience of the whole community, which makes Herta Müllerʼs work enduringly relevant.